Techno-Edutainment as a Learning Strategy for Enhancing Student Engagement in Islamic Religious Education at Muhammadiyah Junior High Schools in Indonesia - Fida Septya Ningsih; Abd. Madjid (Yayasan Insan Mulia Bima, 2026)
Student passivity remains a persistent challenge in Islamic Religious Education, particularly in ISMUBA (Al-Islam, Muhammadiyahan, and Arabic) learning at the junior high school level. While previous studies have examined digital learning and edutainment in general education contexts, limited research has explored the implementation of techno-edutainment in ISMUBA learning. This study investigates how techno-edutainment is implemented, the digital media utilized, and its impact on student engagement in ISMUBA learning at SMP Muhammadiyah 1 Gamping. Employing a qualitative case study design, data were collected through in-depth interviews with three ISMUBA teachers, classroom observations, and document analysis. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, involving data condensation, data display, and conclusion drawing and verification. The findings reveal that techno-edutainment was implemented through the integration of digital and interactive media, with Canva, learning videos, and gamified digital quizzes emerging as the most frequently used tools. These media enhanced student engagement by increasing participation, classroom interaction, responsiveness, and enthusiasm during learning activities. The study also found that the effectiveness of techno-edutainment depended on teachers digital competence, instructional design, and the availability of technological infrastructure. These findings demonstrate that techno-edutainment can serve as an effective pedagogical approach for fostering student engagement in Islamic Religious Education while supporting more interactive and meaningful learning experiences. Sustainable implementation depends on teachers’ ability to integrate technology into pedagogically meaningful learning activities supported by appropriate instructional planning and digital competence.